(untitled) (Revista Investigación & praxis en CS Sociales, 2025)
The objective of the research was to strengthen the basic learning processes of reading and writing through ludic-pedagogical strategies. These strategies were based on Piaget’s cognitive theory and Ludopedagogy. The study was conducted with a sample of 18 preschool children from the educational institution Ana Joaquina Rodríguez de Cañaverales. It was inserted in the qualitative approach and the pedagogical action research design, using field diaries and checklists as instruments. The results showed that 100% of the children were able to imitate actions, assign meanings to objects, and group elements by common characteristics, developing skills of the preoperational stage. They manipulated materials in their own environment and participated in play activities, favoring the connection between play and learning. In literacy, 94.4% demonstrated skills in reading syllables, words, and phrases. It was concluded that the play strategies were effective in strengthening reading and writing skills in preschool students.